Bolsonaro, China and the Indo-Pacific: Challenges in Sight | Bolsonaro, China e o Indo-Pacífico: desafios à vista - Gabriel, João Paulo Nicolini; Mandelbaum, Henoch Gabriel; Sanches Siqueira Campos, André; Carvalho, Carlos Eduardo (Mural Internacional, 2019)
This essay aims to focus on the initial perspectives about Brazil’s foreign policy and strategic thinking on how to cope with the rise of China’s economic and political might since the inauguration of Jair Bolsonaro’s administration. Bolsonaro demonstrates an interest in approach to the United States’ grievances against China. This paper advocate this strategy faces some hurdles: geographical and economic issues constrain countries such as Australia, India, and Japan to assume assertive instances against China, although they present uneasiness with the Chinese regional ambitions and Washington’s demands of a more active role in the Indo-Pacific. These countries compose with the United States the so-called Quadrilateral Security Dialogue, an initiative that seeks to facilitate their policy coordination towards the Indo-Pacific. However, Canberra, Tokyo, and New Delhi uphold a pragmatic strategy in order to maintain their special ties with the United States and to avoid skirmishes with Beijing. Keywords: Brazilian Foreign Policy; China; Indo-Pacific. RESUMO Este ensaio pretende focar nas perspectivas iniciais sobre a política externa e o pensamento estratégico do Brasil sobre como lidar com a ascensão do poder econômico e político da China desde a posse do governo de Jair Bolsonaro. Bolsonaro demonstra interesse em se aproximar das queixas dos Estados Unidos contra a China. Este artigo defende que essa estratégia enfrenta alguns obstáculos: questões geográficas e econômicas impedem que países como a Austrália, a Índia e o Japão assumam posições assertivas contra a China, embora apresentem desconforto com as ambições regionais chinesas e as exigências de Washington de um papel mais ativo no Indo-Pacífico. Esses países compõem, ao lado dos Estados Unidos, o chamado Diálogo Quadrilateral de Segurança, uma iniciativa que busca facilitar sua coordenação política em direção ao Indo-Pacífico. No entanto, Canberra, Tóquio e Nova Déli mantêm uma estratégia pragmática para manter seus laços especiais com os Estados Unidos e evitar confrontos com Pequim. Palavras-chave: Política Externa Brasileira; China; Indo-Pacífico. Recebido em: 11 fev.2019 | Aceito em: 2 mai.2019 DOI: 0.12957/rmi.2019.40103